Impact of maternal early life maltreatment and maternal history of depression on child psychopathology: mediating role of maternal sensitivity? - Bödeker, Katja; Fuchs, Anna; Kaess, Michael; Möhler, Eva; Neukel, Corinne; Zietlow, Anna-Lena; Herpertz, Sabine; Brunner, Romuald; Resch, Franz (Child psychiatry & human development, 2019)
The study addresses the impact of maternal early life maltreatment (ELM) and maternal history of depression (HoD) on offspring’s mental health. Maternal sensitivity was examined as a potential mediator explaining the relationship between maternal ELM, maternal HoD and child psychopathology. Participants were 194 mothers with and without HoD and/or ELM as well as their children between 5 and 12 years. Maternal sensitivity was assessed using the Emotional Availability Scales. Parent and teacher ratings were utilized to assess child psychopathology. Path analyses showed an indirect effect of maternal HoD on parents’ ratings of child psychopathology with maternal sensitivity as mediating variable. In contrast, maternal ELM was directly linked to teachers’ ratings of child psychopathology; this effect was not mediated by maternal sensitivity. Our results indicate that the impact of maternal HoD, maternal ELM, and maternal sensitivity on offspring psychopathology might vary depending on the context in which child psychopathology is assessed.